COVID-19 vaccine hesitancy in Africa: a call to action - Mutombo, Polydor Ngoy; Fallah, Mosoka P; Munodawafa, Davison; Kabel, Ahmed; Houeto, David; Goronga, Tinashe; Mweemba, Oliver; Balance, Gladys; Onya, Hans; Kamba, Roger S; Chipimo, Miriam; Kayembe, Jean-Marie Ntumba; et al. (Elsevier, 2022)
In addition to low COVID-19 vaccine coverage in Africa due to vaccine nationalism and vaccine diplomacy, the gradual effort to distribute COVID-19 vaccines to low-income and middle-income countries (LMICs) is threatened by vaccine hesitancy. In Africa in particular, the low vaccine coverage1 and the ubiquitous vaccine hesitancy in a concerning proportion of the population undermine efforts to fight the COVID-19 pandemic. We advocate for humane, culturally relevant, and rapid public health action to address these issues.